Impact of Public Policy Measures on the German Real Estate Market - Oertel, Christopher Yvo.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2016)
Christopher Oertel studies the impact of public policy measures on the German real estate market and confirms the assumptions, which imply that a city can influence its economic position in relation to nearby cities in the short run by making use of this tax instrument. His analyses begin with an examination of the German residential real estate market from a consumption good perspective. The findings indicate that the home-ownership allowance had a distorting effect by capitalizing into residential real estate prices, although at lower than expected rates. Then the author studies the German residential real estate market from an investment good perspective. Investigating an important amendment of the German tenancy legislation, there is a positive, yet insignificant relationship between the tenancy law reform act and the development of the cap rate. The analysis is completed by focussing on the German office market and investigating how its rental levels and gross purchase prices are affected by changes in the municipal trade tax multiplier. Contents Home-Ownership Allowance and Residential Real Estate Prices Tenancy Law Reform Act of 2001 and Risk Perception of Residential Real Estate Investments Municipal Trade Tax Multiplier and Office Purchase Prices and Rents Target Groups Researchers, students and practitioner in the field of real estate investment About the Author Dr. Christopher Yvo Oertel wrote his dissertation at the Real Estate Management Institute (REMI) of the EBS European Business School.
Introduction -- The Home-Ownership Allowance and Residential Real Estate Prices -- The Tenancy Law Reform Act of 2001 and the Risk Perception of Residential Real Estate Investments -- The Municipal Trade Tax Multiplier and Office Purchase Prices and Rents -- Summary, Practical Implications, and Further Research.
Keywords: Business; Real estate management; Finance; Business and Management; Real Estate Management; Finance, general; Electronic books